1963
DOI: 10.1152/jappl.1963.18.5.924
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics of collapsible vessels with tone: the vascular waterfall

Abstract: A theoretical analysis is presented of pressure-flow relationships in arterioles based on the assumption that the presence of active tension produced by smooth muscle contraction causes a critical closing pressure which is itself a function of the magnitude of the active tension. This analysis differs from those previously carried out in that it uses the pressure-flow relationships of a waterfall rather than those described by Poiseuille's law to characterize the flow between arterioles and capillaries in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
215
0
5

Year Published

1970
1970
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(231 citation statements)
references
References 0 publications
11
215
0
5
Order By: Relevance
“…6 Studies of other organs have shown that the EDP can be determined by a Starling resistor located at arteriolar level. 38 These studies verified the theory of Permutt and Riley 39 showing that two forces, the extramural pressure (ICP in the case of the brain) and arteriolar wall tension determine CCP. Arteriolar wall tension arises from a combination of the stretched elastic components of the vessel wall and active contraction of vascular smooth muscle.…”
Section: Discussionsupporting
confidence: 68%
“…6 Studies of other organs have shown that the EDP can be determined by a Starling resistor located at arteriolar level. 38 These studies verified the theory of Permutt and Riley 39 showing that two forces, the extramural pressure (ICP in the case of the brain) and arteriolar wall tension determine CCP. Arteriolar wall tension arises from a combination of the stretched elastic components of the vessel wall and active contraction of vascular smooth muscle.…”
Section: Discussionsupporting
confidence: 68%
“…Mathematical modeling of the respiratory system has been crucial to the development and advancement of a quantitative understanding of lung physiology in general, and mechanics in particular (2,(60)(61)(62). This approach has become increasingly important with the explosion of information at the cellular and molecular levels, and the integration of quantitative models of physiology at multiple scales and for multiple organ systems is the goal of the International Union of Physiological Sciences Physiome Project (63,64).…”
Section: Image-based Modelingmentioning
confidence: 99%
“…Various analogies can be used when teaching the interaction between cardiac output, venous return, arterial pressure, and oxygen delivery. [1][2][3] However, students may still be confused when they try to integrate these analogies into a single comprehensive mental model. Herein, we propose an ''advance organizer'', namely, gardening to teach hemodynamics to medical students.…”
Section: To the Editormentioning
confidence: 99%